Financial literacy of modern students - Marchenko, K. (НГУ, 2018)
According to the data of the article “Skye Bank marks World Savings Day” World Savings Day is “an event created to increase the public’s awareness of the importance of savings both for modern economies and for individuals alike. Savings is important in the global economy and every depositor contributes to its development”. World Savings Day is a European holiday that is traditionally celebrated on October 31.
Keywords: World Savings Day; modern economies; Savings; global economy